Sosialisasi Kesantunan Berbahasa dalam Penggunaan Aplikasi Whatsapp di Kalangan Remaja Desa Sawangan Kecamatan Leksono Kabupaten Wonosobo - eko prasetyo (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
In linguistics, the language we speak is a reflection of ourselves. People who speak politely will show a good personality. On the other hand, people who speak harshly, cursing, and criticizing show a bad personality. This is what social media users often forget. Indifference, impolite language results in misunderstandings. In oral and written communication, the language used must pay attention to politeness. In this digital era, teenagers and adults dominate the use of social media. Unfortunately, there are still many cases of using language that is not polite on social media which has a bad impact on the perpetrators. One of the impacts is that the perpetrators are caught in legal problems because of the words they say on social media. The use of language that is not polite occurs because of the lack of awareness of social media users regarding patterns of language politeness, especially those who are still teenagers, so this activity aims to provide knowledge to teenagers about language politely on social media and knowledge of the ITE Law. The hope to be achieved from this activity is that teenagers in Sawangan Village, Leksono District, Wonosobo Regency can apply the use of polite language when using social media and avoid using language that is less polite so that they avoid legal cases. Keywords: Politeness, Whatsapp